28. Diagnostic traditional medicine criteria of Covid-19 by using latent tree model (Vietnam Journal of Community Medicine, 2025)
Objectives: In order to treatment result underlying the traditional medicine theory, differentiating disease patterns is important. Thence, this study was implemented to initially establish diagnostic criteria of the mild level of Covid-19 by using lattern tree analysis.Materials and Methods: Step 1: By literatures review, appropriate traditional medicine paterns and manifestations of COVID-19 identified in textbooks and various resources were collected and analized to compose a questionaire. Step 2: Recruiting and investigating COVID-19 patients at mild stage at Hochiminh City traditional medicine hospital by inclusion criteria. Included data were analized by using the Latent tree model analysis.Results: A 65-question survey was used to investigate 438 patients who are appropriate with inclusion criteria. After modeling, 20 latent variables (Y0 to Y20) were established, referring to the groups of included symptom variables. According to Tam tieu (sanjiao) diagnosis theory, there are 2 traditional medicine disease patterns matching with the literatures: Thuong tieu (upper jiao), Trung tieu (middle jiao).Conclusions: Utilizing the Latent tree model analysis, 2 traditional medicine disease patterns of COVID-19 at mild stage were pointed, including: Thuong tieu (upper jiao), Trung tieu (middle jiao).
Keywords: COVID-19 a mild stage; Tam tieu; Latent tree model